Efficiency of Ranking Implementation in University Management System: Practical Experience - V. V. Lazarenko; V. A. Lipatov; T. A. Oleynikova; D. A. Severinov; N. B. Filinov (Высшее образование в России)
One of the biggest challenges facing Russian higher schools administrations is a necessity of management system modernization. That is why in the present study we aimed to measure the effectiveness of a new innovative ranking system implemented at Kursk State Medical University, and finding the part of personal teacher rating determined by his scientific activity. Methods: As criteria for this study, we used data, obtained during an external audit, performed by Interdepartmental monitoring commission in higher educational institutions of Russian Ministry of Education in 2013–2017. Higher school administration, as well as university teachers, could directly affect these rates by making of administrative decisions and act more like scientist or teacher. Results: In 2017, level of integral rate called «Scientific and research activities» showed 2.2 time increasing if compared to 2013. Meanwhile, next rates (per 100 university teaching staff workers) also increased: citation number in Web of Science and Scopus (in 31,6 times), citation number in Russian Science Citation Index (in 22,5 times), number of publications in Web of Science and Scopus (in 2,5 times) and number of research and development projects (in 2 times). According to these measures, we can conclude that levels of scientific activity carry on large part in university rating and appear to be easiest productivity indicators to manage. Practical implications: At the end of the article the authors present recommendations for increasing scientific ranking levels for high schools administrations.